EXPLORING THE POTENTIAL OF FACEBOOK FOR BLENDED LEARNING - Patrisius Istiarto Djiwandono (Celt: A Journal of Culture, English Language Teaching & Literature, 2015)
The paper reports a small-scale exploratory research into the potential of Facebook for blended learning. It sets out to find answers to two research objectives: (1) ) identify the learners' opinions about the use of Facebook as a means of learning reading and job interview in English, and (2) determine the effect', of blended learning on the learners' mastery of new vocabulary. Twenty-five freshmen students of class 2008 who were taking English class at Ma Chung University were taken as the respondents. After a pre-test was administered to them to identity their initial vocabulary mastery, an online task was assigned to them. The task required them to learn interview techniques, upload their own interview session, and read texts. A face to face interaction followed to deal with difficulties and clarify some issues. A post-test measuring their vocabulary growth and questionnaires to identify their opinions were then given at the end of the experiment. The result shows that while gaining significantly higher mastery of new words, the learners expressed different opinions on the use of Facebook as a means of blended learning. The majority felt that face-to-face interaction still needs to accompany the online session to clear up some difficulties and misunderstanding during the online session, while a few others opted for exclusively online session because of its efficiency and higher participation rate by passive learners.